Shaking table tests on seismic behavior of polypropylene fiber reinforced concrete tunnel lining. (June 2019) - Xin, C.L.; Wang, Z.Z.; Zhou, J.M.; Gao, B.
Highlights: The effect of the polypropylene fiber reinforced concrete as secondary lining reducing the seismic response of tunnel structure was explored. The comparison shows that the polypropylene fiber changed the brittle behavior of PC and the damage patterns of RC along with the distribute paths of cracks. Abstract: Fiber reinforced concrete has been a widely applied durable material in ground structures or as the primary support in underground structures in the form of shotcrete. Whereas, fiber reinforced concrete was seldom utilized as secondary lining in underground structures, much less the polypropylene fiber reinforced concrete. Currently, many researches about fiber reinforced concrete have attempted to study tunnel linings behavior mostly in static state but fiber reinforced concrete has more advantages in seismic dynamic circumstance. A shaking table-based method to determine the behavior of polypropylene fiber reinforced concrete as tunnel lining can be the ideal method to study its response mechanism in seismic dynamic states. This paper presents results from a series shaking table tests on scaled tunnel models with the plain concrete (PC), steel reinforced concrete (RC) and polypropylene fiber reinforced concrete (PFRC) under increasing seismic intensities excitations. This research aims to explore the polypropylene fiber reinforced concrete as secondary lining reducing the seismic response intensity of tunnel structure. The comparison demonstrates that low tensile strength and brittle behavior at low strain are the two significant shortcomings of plain concrete. Concrete destruction, mortar destruction and cement pastes destruction are the three levels can describe the damage process of plain concrete. The three main roles of polypropylene fiber in concrete lie in polypropylene fiber strength, toughness and resistance to split. Polypropylene fiber changes the brittle behavior of PC and the damage patterns of RC along with the distribute paths of cracks. Besides, polypropylene fiber is able to effectively minimize the amount of initial micro cracks, postpone the appearance of new cracks, prevent the propagation of macro cracks and relieve the stress concentration at the ends of fibers. Polypropylene fiber allows tunnel lining to generate smaller deformations and strains to resist deformations of surrounding rock, which is more suitable to be applied in the large deformation sections of tunnel lining in soft surrounding rock. It is important to choose the suitable lining materials in terms of seismic intensity to take full advantage of the aseismic performance. The above research results can provide reference for polypropylene fiber reinforced concrete design and further research as tunnel lining.